2002
DOI: 10.3349/ymj.2002.43.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metabolism and Bone Mineral Density in Premenopausal Women with Mild Depression

Abstract: This study was undertaken to investigate the bone metabolism and bone mineral density (BMD) in female patients suffering from depression. Forty-two female patients diagnosed with depression and 42 healthy women, all in the premenopausal age, were enrolled. A clinical evaluation, measurements of the biochemical markers of bone metabolism and BMD measurements were performed. The BMD values were found to be similar in all measured sites. It was concluded that a low BMD was not a prominent feature of premenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 0 publications
2
38
0
6
Order By: Relevance
“…The majority of analyses have replicated the original 1994 finding of Schweiger et al lower BMD among persons with depression or depressive symptoms relative to comparison groups [7][8][9][10][11][12][13][14][15][16][17][18]. However, seven studies have not found a statistically significant association between depression or depressive symptoms and lower BMD [19][20][21][22][23][24][25]. These studies are discussed below under their respective study designs.…”
Section: Depression Depressive Symptoms and Osteoporosissupporting
confidence: 48%
See 2 more Smart Citations
“…The majority of analyses have replicated the original 1994 finding of Schweiger et al lower BMD among persons with depression or depressive symptoms relative to comparison groups [7][8][9][10][11][12][13][14][15][16][17][18]. However, seven studies have not found a statistically significant association between depression or depressive symptoms and lower BMD [19][20][21][22][23][24][25]. These studies are discussed below under their respective study designs.…”
Section: Depression Depressive Symptoms and Osteoporosissupporting
confidence: 48%
“…The case-control study by Amsterdam and Hooper (1995) had limited power to detect an effect given the small sample size (N=11) [20]. Similarly, the studies by Kavuncu et al (2002) and Yazici et al (2005) were limited to young pre-menopausal women (mean age of depressed group: 35.4 years and 44.8 years, respectively). Many of these women had not yet passed through the peak developmental period of risk for depression (age 30-45) [27], and thus the cases of depression in these reports may not have been representative of the depression in the general population.…”
Section: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause, aging, deficient calcium and vitamin D intake, smoking, alcohol use, immobility, drugs, hormonal and renal diseases have been suggested for the etiology of OP [4][5][6]. In recent years major depression has been also demonstrated as a risk factor in the development of OP [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations reported no difference in serum markers of bone turnover, including osteocalcin, bone-specific alkaline phosphatase and telopeptide (C-and N-terminal), in depression cases compared with controls, even when differences in BMD were found [25][26][27][28][29][30]. With few exceptions [24,29], the majority of studies have reported no difference between depression cases and controls concerning calcium metabolism indicated by levels of parathyroid hormone or 25-OH vitamin D levels [25,27,28,30,31]. The inconsistency of the existing evidence regarding depression and markers of bone turnover probably stems from issues pertaining to study design, including small sample sizes and differing sample composition, the lack of longitudinal analyses or studies in men, and the risk of residual confounding from unaccounted variables, including psychotropic medication use and chronic medical conditions.…”
mentioning
confidence: 99%